Adenosine A2A Receptors as Biomarkers of Brain Diseases - Moreira-de-Sá, Ana; Lourenço, Vanessa S.; Canas, Paula M.; Cunha, Rodrigo A. (Frontiers in Neuroscience, 2021)
Extracellular adenosine is produced with increased metabolic activity or stress, acting as a paracrine signal of cellular effort. Adenosine receptors are most abundant in the brain, where adenosine acts through inhibitory A1 receptors to decrease activity/noise and through facilitatory A2A receptors (A2AR) to promote plastic changes in physiological conditions. By bolstering glutamate excitotoxicity and neuroinflammation, A2AR also contribute to synaptic and neuronal damage, as heralded by the neuroprotection afforded by the genetic or pharmacological blockade of A2AR in animal models of ischemia, traumatic brain injury, convulsions/epilepsy, repeated stress or Alzheimer’s or Parkinson’s diseases. A2AR overfunction is not only necessary for the expression of brain damage but is actually sufficient to trigger brain dysfunction in the absence of brain insults or other disease triggers. Furthermore, A2AR overfunction seems to be an early event in the demise of brain diseases, which involves an increased formation of ATP-derived adenosine and an up-regulation of A2AR. This prompts the novel hypothesis that the evaluation of A2AR density in afflicted brain circuits may become an important biomarker of susceptibility and evolution of brain diseases once faithful PET ligands are optimized. Additional relevant biomarkers would be measuring the extracellular ATP and/or adenosine levels with selective dyes, to identify stressed regions in the brain. A2AR display several polymorphisms in humans and preliminary studies have associated different A2AR polymorphisms with altered morphofunctional brain endpoints associated with neuropsychiatric diseases. This further prompts the interest in exploiting A2AR polymorphic analysis as an ancillary biomarker of susceptibility/evolution of brain diseases.